Organizational Principles of Hyporheic Exchange Flow and Biogeochemical Cycling in River Networks Across Scales. Issue 3 (24th February 2022) - Krause, Stefan; Abbott, Benjamin W.; Baranov, Viktor; Bernal, Susana; Blaen, Phillip; Datry, Thibault; Drummond, Jennifer; Fleckenstein, Jan H.; Velez, Jesus Gomez; Hannah, David M.; Knapp, Julia L. A.; Kurz, Marie; et al.
Abstract: Hyporheic zones increase freshwater ecosystem resilience to hydrological extremes and global environmental change. However, current conceptualizations of hyporheic exchange, residence time distributions, and the associated biogeochemical cycling in streambed sediments do not always accurately explain the hydrological and biogeochemical complexity observed in streams and rivers. Specifically, existing conceptual models insufficiently represent the coupled transport and reactivity along groundwater and surface water flow paths, the role of autochthonous organic matter in streambed biogeochemical functioning, and the feedbacks between surface‐subsurface ecological processes, both within and across spatial and temporal scales. While simplified approaches to these issues are justifiable and necessary for transferability, the exclusion of important hyporheic processes from our conceptualizations can lead to erroneous conclusions and inadequate understanding and management of interconnected surface water and groundwater environments. This is particularly true at the landscape scale, where the organizational principles of spatio‐temporal dynamics of hyporheic exchange flow (HEF) and biogeochemical processes remain largely uncharacterized. This article seeks to identify the most important drivers and controls of HEF and biogeochemical cycling based on a comprehensive synthesis of findings from a wide range of river systems. We use these observations to test current paradigms and conceptual models, discussing the interactions of local‐to‐regional hydrological, geomorphological, and ecological controls of hyporheic zone functioning. This improved conceptualization of the landscape organizational principles of drivers of HEF and biogeochemical processes from reach to catchment scales will inform future river research directions and watershed management strategies. Key Points: The complexity of HZ rivers and controls exceeds the range of conditions considered in previous conceptualizations and model formulations Understanding organizational principles of hyporheic exchange flow (HEF) and biogeochemical cycling in landscapes is key for generalizing process knowledge Local HEF, metabolism, and biogeochemical cycling are embedded within the larger context of fluvial and terrestrial ecosystem structure